Characteristics of Upper Extremity Trauma Patients from Division of Orthopedics and Traumatology in Department of Surgery Dr. Mohammad Hoesin General Hospital Since Januari 1st - December 31st 2019 - Ridnia Nur Istiqomah; Wiria Aryanta (Sriwijaya Journal of Surgery, 2021)
Background: Upper extremity trauma is one of the most frequent of trauma that leads to emergency department visitation in every health care facilities. A wide range of manifestations could differently be present from one area to another. Thus, the statistical prevalence number of upper extremity trauma is very important for designing and optimizing the health care service for the purpose of preventive and curative. This study aims to understand the charachteristics of patient with upper extremity trauma that admitted at Dr. Mohammad Hoesin General Hospital Palembang emergency department in the period of January to December 2019. Methods: This research was an observational descriptive study. Using secondary data from the medical records of Mohammad Hoesin Hospital, Palembang. Performed in the from January 2019 to December 2019. Samples were all upper extremity trauma patients who were admitted at Dr. Mohammad Hoesin General Hospital Palembang emergency department in the period of study. Results: There were 54 subjects participated who met the study’s criterias. Most of them were male (76%) with the average of age around 34 years old. It is also dominated with the group of age 25-44 years old (39%), 80% of among all patients have closed and hard tissue trauma. Regio humerus is the most frequent area impacted (16 patients). Most of the patients have worked as private employees (13 patients) with education background till senior high school (38 patients). The etiology of majority trauma is traffic accident (29 patients) that lived outside Palembang area (16 patients). Conclusion: Majority of the upper extremity trauma cases of this study have characteristics as male in productive group of age and the cause of trauma is traffic accident.